Treatment of Devital Permanent Anterior Teeth with Incomplete Root Development - Yagubaga, Aliyev Tarlan; Vahid, Piriyev Ramin; Agaveli, Ibragimov Elshad; Ilham, Akhmedov Said (American Journal of Biology and Natural Sciences, 2025)
When treating post-traumatic teeth in children, special attention should be paid to the use of regenerative endodontic techniques, especially in cases where root development is incomplete and even the use of mineral trioxide aggregate does not contribute to the improvement of the tooth condition.